A new ductile failure criterion for micro/meso scale forming limit prediction of metal foils considering size effect and free surface roughening. (October 2022) - Zheng, Lihuang; Wang, Kun; Jiang, Yuanyuan; Wan, Min; Meng, Bao
Highlights: A general theoretical framework for ductile failure prediction considering size effect and free surface roughening is provided. An innovative ductile failure criterion is proposed for predicting micro/meso scale forming limits of metal foils. The primary mechanism of size effect on forming limits under various strain paths is revealed. Analytical descriptions of size effect on stress state are established. The validity of the proposed failure criterion is verified via actual forming processes. Abstract: For the establishment of reliable micro/meso scale forming processes, it is essential to accurately predict the forming limits of metal foils under different deformation paths. However, existing uncoupled ductile failure criteria cannot accurately forecast the micro/meso scale forming limits of metal foils affected by size effect in the whole strain path range of forming limit curve (FLC). To deal with the issue, a new ductile failure criterion is proposed in this paper based on the theoretical analyses of size effect affected void nucleation, growth, and coalescence, as well as free surface roughening affected critical damage of metal foils. A method for identifying the material parameters of the proposed ductile failure criterion coupled with a modified Yld2000 yield criterion is provided, and the size effect on micro/meso scale FLCs forecasted by the proposed ductile failure criterion is discussed. In addition, the forming limit strains of SUS304 and pure copper foils with different thicknesses and grain sizes are employed to reveal the prediction capability of the new ductile failure criterion. Comparisons between the experimental results and the FLCs constructed by the proposed failure criterion demonstrate that the proposed failure criterion can accurately predict the forming limits of metal foils affected by size effect between uniaxial tension (UT) and equi-biaxial tension (EBT). To further show the prediction capability of the proposed failure criterion in actual micro/meso scale forming processes, the limit drawing ratio of a SUS304 foil and local maximum forming heights in micro-channel hydroforming for pure copper foils are predicted using the new failure criterion combined with the finite element method, and the predicted results are compared with experimental results. Comparative research demonstrates that the proposed ductile failure criterion can accurately forecast the forming limits of metal foils affected by size effect in actual micro/meso scale forming processes. Graphical abstract: Image, graphical abstract .